Role of Sowing Time in Maize Production (Review) - Rácz, Ferenc; Illés, Ottó; Pók, István; Szőke, Csaba; Zubori, Zsuzsanna (Acta Agraria Debreceniensis, 2003)
Many authors, both in Hungary and abroad, have reported on experiments carried out to determine the role of sowing time in maize, but the results are often contradictory. This is hardly surprising, since the maize plant exhibits enormous genetic variability and the hybrids created through selection and inbreeding may have very specific requirements as to sowing date. The year effect, too, often complicates the efforts of scientists to provide clear guidance to farmers on the optimal sowing date for each hybrid.